Social cohesion in Asia: origins, contemporary shapes and future dynamics - Croissant, Aurel; Walkenhorst, Peter (Routledge, Taylor & Francis Group, 2020)
"This book explores the historical origins, contemporary dynamics and future challenges of social cohesion in South, Southeast and East Asia-one of the most dynamic and at the same time heterogeneous regions in the world, in terms of economic, political and human development. The comparative case studies in this volume develop a better understanding of social cohesion in Asia by exploring how social cohesion is understood, analyzed and sometimes politically instrumentalized. Examining different dimensions and qualities of social cohesion and how they are linked together, it also discusses the challenges of social cohesion in individual societies. The case studies include examples from Bangladesh, India, Sri Lanka, Indonesia, Myanmar, Singapore, South Korea and Mainland China and building on the conceptual work and empirical findings of the Asian Social Cohesion Radar, this book provides detailed cross-country analyses over the past fifteen years. Combining rigorous conceptual and theoretical reasoning with a systematic empirical analysis of trends across the region, Social Cohesion in Asia will be of great interest to students and scholars of Asian politics, international relations, political sociology, comparative politics and Democratization Studies"--
Includes bibliographical references and index
Keywords: Asia -- Social conditions; Asia -- Social policy; Aufsatzsammlung; Geschichte; Gesellschaft; Gruppenkohäsion; Asien